Pro-Poor Urban Adaptation to Climate Change : Based on Case Studies in Kenya and Nicaragua - Moser, Caroline (World Bank, Washington, DC, 2012)
Poor urban populations in Southern cities are already experiencing the negative impacts of changing weather patterns associated with climate change and climate variability and future projections suggest that these impacts will get worse. Severe weather patterns, experienced as prolonged droughts, intense rainfall or wind speed cause substantial damage to the assets and well-being of city-dwellers, causing localized flooding, housing damage, economic loss, and posing dangers to health and educational achievement. Yet, severe weather events that do not register as disasters on the national or international screen are rarely addressed in the context of climate change adaptation. Urban governments face a number of constraints to effectively address and build resilience to severe weather: a knowledge constraint (given the scarce evidence of the impact of ongoing severe weather trends), in addition to institutional and fiscal limitations. Since most climate vulnerability research in urban centers has focused on projections and capacity building for disaster events, city adaptation plans, where developed, has also centered on establishing disaster prevention and preparedness systems. This note presents results from field studies of Mombasa, Kenya, and Esteli in Nicaragua looking at the experience of poor urban communities in relation to their changing experience of weather and its impact on their lives. These studies applied a participatory urban methodology by which local city governments and the Non-governmental Organizations (NGOs) and donors that support them - can address adaptation and resilience to severe weather. It finds that talking to poor urban communities is essential in order to understand the vulnerability and adaptation solutions to severe weather. It also notes that existing financial mechanisms at the city level, including local and community-based organizations, can be used to support low-cost solutions that enhance the resilience of the most vulnerable city-dwellers.